On Certain Aspect of Leaf Development in Aren (Arenga pinnata L) - E.B. Hidajat; B.I. Utomo (Journal of Mathematical and Fundamental Sciences, 1976)
Abstract. In Arenga pinnata fold formation leading to the establishment of the future pinnae occurs by differential growth. During the development the abaxial ridges grow more rapidly than the axial ones resulting in a bending of the ridges to the adaxial side while the direction changes from horizontal, to oblique vertical. This leads to a crowding up of the adaxial ridges adaxial to the rachis. A covering or haut develops then extension growth of the nonplicate lamina over the adaxial ridges mentioned there by uniting them in a composite structure. The two parts fuse along the central meeting line, forming one continuous covering. The huge tubular ligule is initiated at the fourth or fifth primordium. At the 7th primordium the ligule encloses all younger leaf primordial. Its highest growth activity is reached about 2 primordia before the sword and the maximum size is held by the primordium before the latter. Penetration of the ligule by the sword initiates its disintegration in a basipetal direction, stops adaxial to the petiole base but proceeds at a slower pace ventrally.